Pencil and paper tricks - Lamb, Geoffrey Frederick (Nashville : T. Nelson, 1977)
Includes step-by-step directions for executing a variety of tricks involving figures, words, and diagrams.
Keywords: Pencil games; Group games; Mathematical recreations; Pencil games; Mathematical recreations; Tricks